Re-weighing the 5% tagging recommendation : assessing the potential impacts of tags on the behaviour and body condition of bats - Meierhofer, Melissa B.; Tena, Elena; Lilley, Thomas M.; Dechmann, Dina K. N.; Voigt, Christian C.; Troitsky, Tanya S.; de Bruyn, Luc; Braun de Torrez; Elizabeth; Eldegard, Katrine; Elmeros, Morten; Gyselings, Ralf; et al. (Wiley-Blackwell, 2025)
Considerable advances and breakthroughs in wildlife tracking technology have occurred in recent years, allowing researchers to gain insights into the movements and behaviours of a broad range of animals. Considering the accessibility and increase in use of tracking devices in wildlife studies, it is important to better understand the effects on these on animals. Our endeavour revisits a guideline established in 1988, which proposes that bats may encounter body condition or health problems and alter their behaviour when carrying tags weighing more than 5% of their body mass. Through a systematic literature review, we conducted a meta-analysis to identify the impacts of tags on bats, including 367 papers from 1976 to 2023 that discussed, mentioned, employed, or quantified tagging of bats. We noted that the proportion of studies exceeding the 5% rule has not changed in recent years. However, the impact of tags was quantified in few studies for behaviour (n = 7) and body condition (n = 10) of bats. We were unable to assess whether tags weighing less or more than 5% of the bat's body mass impacted bats, but our meta-analysis did identify that tags, irrespective of mass, affect the behaviour and body condition of bats. Although the overall magnitude of measured effects of tags on bats was small, progress has been made to advance our understanding of tag mass on bats. Naturally, there is a bias in reporting of significant results, illustrating the need of reporting results when there is no apparent effect of tags on bats. Our findings highlight the need for rigorous reporting of behaviour and body condition data associated with tagging of animals and illustrate the importance for studies comparing how tracking devices of different dimensions and masses may impact bat species to ensure research meets rigorous ethical standards.Impacts of tags on different behaviours and body condition measures of bats.image